Analisis Strategi Marketing Communication Melalui Instagram dalam Membangun Engagement Audiens di InterContinental Bali Sanur Resort - Luh Sintya Rismayanti; I Gusti Agung Alit Suryawati (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the marketing communication strategy implemented by InterContinental Bali Sanur Resort by IHG through Instagram social media in building engagement and strengthening relationships with customers. The background of this research is based on the increasing role of social media as a marketing communication tool in the hospitality industry, where Instagram has become an effective platform for showcasing guest experiences, building brand image, and reaching a wider audience. This research uses a descriptive qualitative approach with data collection techniques through interviews, observation, and content analysis of the Instagram account @intercontinentalbalisanurresort during the period January–May 2026. The focus of the study is directed toward content management, utilization of Instagram features, and interaction strategies conducted by the hotel with its audience. The results show that InterContinental Bali Sanur Resort utilizes Instagram by presenting visual content that highlights resort facilities, wellness experiences, guest activities, restaurant promotions, MICE and wedding events, as well as tourist destinations around Sanur. In addition, the hotel also utilizes Story, Feed, Reels, User Generated Content (UGC), and collaborations with influencers to increase audience reach and engagement. This study concludes that Instagram not only functions as a promotional medium, but also as a platform for creating digital experiences, increasing engagement, and strengthening brand image in the increasingly competitive hospitality industry.